Membrane distillation—Principles, applications, configurations, design, and implementation - Nidal Hilal (Emerging Technologies for Sustainable Desalination Handbook, 2018)
Membrane distillation (MD) is a promising technology for treating saline water and wastewater with high rejection factors, which cannot be accomplished by conventional technologies. MD is a thermally driven separation process in which only the vapor molecules pass through a microporous hydrophobic membrane. The driving force in the MD process is the vapor pressure difference induced by the temperature difference across the membrane surface.